THU0161 ORAL VERSUS SUBCUTANEOUS METHOTREXATE IN RECENTLYDIAGNOSED RHEUMATOID ARTHRITIS: DO WE GET THE SAME RESULTS?. (June 2019) - Silke, Linda; Anzola Alfaro, Ana Melissa; Caballero Motta, Liz R.; Torrens Cid, Luis A; Y Soleto, Christian; Trives Folguera, Laura; F Lopez, Katherine; Silva Riveiro, Alicia; Lopez-Ceron Cofio, Ana; Martinez-Barrio, Julia; Ovalles, Juan; Serrano Benavente, Beln; et al.
Abstract : Background: As we know, the use of disease modifying antirheumatic drugs (DMARDs) improves the overall prognosis of rheumatoid arthritis (RA) specially when treatment is started early in the course of the disease. The most widely used DMARD is methotrexate (MTX) mainly because of its favorable efficacy-toxicity ratio. However, there is a lot of variability using MTX when it comes to dosage and route of administration; and little research on the overall response of patients to the different strategies used. Objectives: To compare the clinical response of oral (PO) versus subcutaneous (SC) MTX in recently diagnosed RA patients with no previous use of DMARDs. We evaluated the data collected at baseline, the 3, 6 and 12 month after the beginning of MTX treatment. Methods: This descriptive, observational, longitudinal retrospective study was achieved using a cohort of patients with recently diagnosed RA in which treatment with MTX was started between August 1 st 2015 to September 1 st 2018. We collected demographic and clinical data, disease activity markers, MTX and corticoid dosage, routes of administration and treatment changes. Results: In total, 52 patients were included of which 39 (75%) were women, with an average age of 57.56 years. There was a mean of 26 weeks between the first symptoms and the beginning of MTX. In the PO MTX group, 8 (32%) patients required a change to SC MTX; in 87.5% of cases due to treatment inefficacy and 7 (87.5%) of these patients kept the SC route until the end of the study. Out of the patients that began with SC MTX, the one that changed route to PO maintained a good response. All the patients with biologic DMARDs kept the SC MTX as adjuvant therapy. On the other hand, the 3 (12%) patients of the PO that used a biologic DMARD had suspended MTX several months before. Both groups had a good response to MTX. There was a significant reduction in corticoid requirements during the first year of treatment(P<0.001 and P 0.03 for PO and SC respectively). At the end of the study, 21 (41%) patients received SC MTX and the number goes up to 25 (49%) if we include those who also had biologic DMARDs. Of those who suspended MTX, 85% were due to adverse effects, similar in both groups. Conclusion: Our study suggests that patients that start with PO MTX require route administration changes more frequently than the SC group during the first year of follow-up. SC MTX was the route used by almost half the patients by the end of the study. We can also see that the inflammatory response to MTX was acceptable regardless of administration route and that corticoids could be reduced significantly in both groups. References: [1] Braun, J. et al. Comparison of the clinical efficacy and safety of subcutaneous versus oral administration of methotrexate in patients with active rheumatoid arthritis: Results of a six-month, multicenter, randomized, double-blind, controlled, phase IV trial. Arthritis Rheum 2008; 58: 73-81. [2] Tornero Molina, J et al. Recommendations for the use of methotrexate in rheumatoid arthritis: Up and down scaling of the dose and administration routes. Reumatol Clin 2015;11:3-8. Disclosure of Interests: None declared